Pemanfaatan Canva sebagai Alat Kreatif untuk Meningkatkan Strategi Promosi GURAFIX: Bisnis Jasa Desain Grafis (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
In the rapidly evolving digital era, business promotion strategies have undergone significant transformations, particularly through the utilization of online graphic design platforms. This study aims to explore the use of Canva as a creative tool to enhance the promotional strategies of GURAFIX, a graphic design service business. The method employed is qualitative with direct observation techniques and portfolio analysis. The findings indicate that Canva plays a crucial role in improving the productivity and efficiency of the GURAFIX team in producing visually appealing content aligned with current market trends. Utilizing Canva has also positively impacted the quality of designs and promotional appeal, contributing to an increase in clients. However, the study also identifies Canva's limitations in meeting advanced design requirements. This research provides practical implications for other graphic design service businesses to optimally utilize Canva as part of their promotional strategies.